The Benefit of Blogging for Archaeology - Cargill, Robert R. 1973- (2010)
Blogging (or "web logging") has evolved from online journaling to a multi-million dollar enterprise involving over 100 million blogs worldwide. And while journalists and news organizations have been quick to adopt blogging as a publishing tool, the academy has been slow to adopt the technology as a legitimate scholarly enterprise. This article argues that blogging is the next logical step for independent scholars and researchers who seek to publish their original work, and that universities should begin accepting blogging as a legitimate scholarly endeavor. Specifically, archaeologists should embrace blogging because of its ease of use, decreased time to publication, affordability, ability to publish multiple forms of media, and for the increased exposure publishing online brings to a scholar’s work. The article details the impact of blogging on existing publishing models, the peer-review process, and discusses the numerous benefits of blogging for archaeology.
Keywords: Archaeology; Blogging; Education; Instruction; peer-review; Publishing; Technology